2023
DOI: 10.1021/acs.iecr.3c00053
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Modeling for Multiphase Processes: Application to a Rotomolding Process

Abstract: This paper addresses the problem of capturing the multiphase nature of a rotational molding process using subspace identification (SSID) to enable improved control. Existing SSID techniques are not designed to utilize any known, multiphase nature of a process in the model identification stage. This work adapts existing SSID methods to account for multiple phases by splitting the data into phases during the identification step and building a distinct SSID model for each phase while carefully connecting the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Key highlights from the study stated that the cooling rate was directly proportional to the degree of warpage and maximum warpage occurred when the greatest temperature difference was evident between the part and mould, offering practical considerations for rotational moulding when experiencing warpage. Ubene and Mhaskar [ 81 ] explored a multiphase model for the rotational moulding process. The authors concluded that a multiphase subspace identification (MPSSID) was introduced with a good degree of success for modelling a three-phase model [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key highlights from the study stated that the cooling rate was directly proportional to the degree of warpage and maximum warpage occurred when the greatest temperature difference was evident between the part and mould, offering practical considerations for rotational moulding when experiencing warpage. Ubene and Mhaskar [ 81 ] explored a multiphase model for the rotational moulding process. The authors concluded that a multiphase subspace identification (MPSSID) was introduced with a good degree of success for modelling a three-phase model [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ubene and Mhaskar [ 81 ] explored a multiphase model for the rotational moulding process. The authors concluded that a multiphase subspace identification (MPSSID) was introduced with a good degree of success for modelling a three-phase model [ 81 ]. Reportedly, the model was tested on pre-existing data from a uniaxial process, and it was found that a three-phase model best predicted the temperature trajectory of the internal air trace, translating into product quality prediction improvements.…”
Section: Resultsmentioning
confidence: 99%